The "Binder Ring" Bypass: Transection, Rerouting, and Reanastomosis as an Alternative to Macrovascular Decompression of a Dolichoectatic Vertebral Artery. Issue 4 (11th April 2022) - Srinivasan, Visish M.; Labib, Mohamed A.; Furey, Charuta G.; Catapano, Joshua S.; Lawton, Michael T.
Abstract : BACKGROUND: In cases of extreme vertebrobasilar dolichoectasia, padding the cranial nerves (CNs) (microvascular decompression [MVD]) and clip-assisted sling transposition of the tortuous artery (macrovascular decompression [MaVD]) may be ineffective because the sling does not reduce the redundancy. Transposition may not decompress the nerves or may kink the artery. An alternative solution is needed. OBJECTIVE: To introduce the "binder ring" bypass as a novel solution to this unusual macrovascular compression problem. METHODS: The binder ring denotes the opening and closing of the offending vascular loop with standard bypass techniques with the artery transected, rerouted lateral to the CNs, and reanastomosed. An example case study is presented for a 72-year-old man whose severe vertebral artery tortuosity could not be relieved by MVD or MaVD. His pathology was exposed with an extended retrosigmoid craniotomy, the V4 segment was transected, the free ends were mobilized lateral to CN VII/VIII, and an end-to-end reanastomosis was performed with intraluminal suturing. RESULTS: The example binder ring bypass was patent angiographically, and the patient experienced immediate and lasting symptom relief without complications. CONCLUSION: The binder ring bypass applies standard bypass techniques to macrovascular compression but represents a significant escalation in technical challenges relative to traditional techniques. Patient tolerance to temporary arterial occlusion during reanastomosis depends on the location of the compressive arterial loop and the anatomy of collateral circulation. The binder ring bypass should be used as a last resort after medical therapy and MaVD techniques fail and performed only by neurosurgeons with advanced bypass skills.